Shown Emotions, Spoken Emotions - Plantin, Christian (Człowiek i Społeczeństwo, 2026)
This paper argues that everyday argumentative episodes are inherently emotional and proposes applying the concepts and methods used to analyze emotional episodes to argumentative-emotional ones. Emotions develop at the verbal and physical (paraverbal) levels. Sections one and two discuss two paraverbal aspects of emotion. The first section presents increased tension as a criterion for identifying the beginning of an emotional-argumentative episode. Section two focuses on the physical transformations individuals experience during emotional interactions and their correlative communicative and argumentative function. This topic is difficult to document adequately and the data are difficult to interpret. It constitutes an autonomous field of study. Sections three through five focus on the lexicon of emotional terms. This lexicon includes hundreds of terms that refer to emotions. In addition to this core set, it includes some thousands of terms that suggest, connote, imply, or point toward an emotion (some thousands). The dictionary-based impact method is a unifying approach to an expanded set of emotional terms.